2010
DOI: 10.2174/157339910790909431
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Maternal and Fetal Growth Factors in Diabetic Pregnancy

Abstract: Diabetes mellitus complicates 1-2% of all pregnancies but is associated with high perinatal morbidity and mortality. Gestational diabetes affects up to 4% of pregnancies and is associated with fetal macrosomia (large for dates). Fetal growth is a complex process influenced by determinants such as genetics, maternal factors, uterine environment and maternal and fetal hormones. Infants of pre-gestational diabetic mothers have an additional influence of maternal fluctuations in glycaemia. The purpose of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 108 publications
2
45
0
4
Order By: Relevance
“…It has been demonstrated that cord blood concentrations of leptin and adiponectin are associated to subsequent BMI and central adiposity in children (21). Therefore, whereas the clinical applications of this data remain speculative, it may be possible that neonatal levels of adipokines and particularly their mutual relationship could be used to identify neonates with increased risk of developing childhood obesity and/or its related complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that cord blood concentrations of leptin and adiponectin are associated to subsequent BMI and central adiposity in children (21). Therefore, whereas the clinical applications of this data remain speculative, it may be possible that neonatal levels of adipokines and particularly their mutual relationship could be used to identify neonates with increased risk of developing childhood obesity and/or its related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin appears to play a role in a number of processes associated with pathological fetal growth, most notably maternal diabetes (21,22). Leptin in umbilical cord blood has been demonstrated to be of fetal origin as it is independent of maternal levels of leptin (23).…”
Section: Introductionmentioning
confidence: 99%
“…Increased fetal weight in the infants of diabetic mothers was previously considered to be the result of maternal hyperglycemia. However, the control of fetal growth in pregnancies with or without underlying diabetes is significantly more complicated (8).…”
Section: Introductionmentioning
confidence: 99%
“…When we perform prospective sampling at defined time intervals we have data that show good correlation with IGF-1/2 levels and birth weight but not with IGFBP-1 and -3 [23,24,37]. Later studies conclude that IGF-1/2 cannot solely explain the complex process of fetal growth, as it is influenced by maternal glycemia as well as genetics, diabetic factors, maternal and fetal hormones [38].…”
Section: Temporal Review Of Studies On Fetal Growth and The Igf Systemmentioning
confidence: 95%